2019
DOI: 10.1021/jacs.8b11447
|View full text |Cite
|
Sign up to set email alerts
|

Few-Nanometer-Sized α-CsPbI3 Quantum Dots Enabled by Strontium Substitution and Iodide Passivation for Efficient Red-Light Emitting Diodes

Abstract: Cubic phase CsPbI3 quantum dots (α-CsPbI3 QDs) as a newly emerging type of semiconducting QDs hold tremendous promise for fundamental research and optoelectronic device applications. However, stable and sub-5 nm-sized α-CsPbI3 QDs have rarely been demonstrated so far due to their highly labile ionic structure and low phase stability. Here, we report a novel strontium-substitution along with iodide passivation strategy to stabilize the cubic phase of CsPbI3, achieving the facile synthesis of α-CsPbI3 QDs with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
228
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(235 citation statements)
references
References 43 publications
(97 reference statements)
7
228
0
Order By: Relevance
“…For instance, the metal halide DP Cs 2 AgBiCl 6 and Cs 2 AgBiBr 6 NCs with good stability under ambient conditions have been synthesized, but the optical properties of the pure phase lead‐free double halide perovskite NCs are unsatisfactory (e.g., low PL quantum yield [PLQY]) for many optical applications 9. Doping “impurities” in semiconducting NCs has aroused great interest because it is efficient to control over the photoelectric properties of NCs and have shown potentials in solar cells,10 light emitting diodes,11 and safety markers 12. Recently, impurity dopants including Mn 2+ , In 3+ , Yb 3+ , Er 3+ , and Eu 3+ have been tried in lead‐free halide DP NCs to endow desirable optical properties in these DP NCs 13.…”
Section: Figurementioning
confidence: 99%
“…For instance, the metal halide DP Cs 2 AgBiCl 6 and Cs 2 AgBiBr 6 NCs with good stability under ambient conditions have been synthesized, but the optical properties of the pure phase lead‐free double halide perovskite NCs are unsatisfactory (e.g., low PL quantum yield [PLQY]) for many optical applications 9. Doping “impurities” in semiconducting NCs has aroused great interest because it is efficient to control over the photoelectric properties of NCs and have shown potentials in solar cells,10 light emitting diodes,11 and safety markers 12. Recently, impurity dopants including Mn 2+ , In 3+ , Yb 3+ , Er 3+ , and Eu 3+ have been tried in lead‐free halide DP NCs to endow desirable optical properties in these DP NCs 13.…”
Section: Figurementioning
confidence: 99%
“…Yao et al demonstrated that stable cubic-phase CsPbI 3 with tunable size from 15 to sub-5 nm through introducing Sr 2 + substitution along with iodide passivation. [85] It was found that the incorporation of Sr 2 + ions significantly increased the formation energies of the perovskite structure and reduced the structure distortion for small-sized CsPbI 3 NCs. The obtained few-nanometer-sized doped CsPbI 3 NCs still retained the high PL emission properties and highly close packing in the deposited thin films, with improved PL stability of the colloidal solution and the thin films.…”
Section: Red-emissive Leds Based On Metal Doped/alloyed Perovskite Ncsmentioning
confidence: 99%
“…The divalent doping strategy of CsPbI 3 NCs can be combined with efficient halide surface passivation to further improve the material properties and the device performance. Yao et al [85] and Lu et al [86] independently demonstrated high performance red-emissive LEDs based on CsPbI 3 NCs with simultaneous strontium (Sr 2 + ) doping and iodide/chlorine surface passivation. Owing to the slightly smaller ion radius of Sr 2 + (118 pm) than the Pb 2 + (119 pm) ions, doping of the Sr 2 + into the CsPbI 3 NCs may cause a slight lattice contraction.…”
Section: Red-emissive Leds Based On Metal Doped/alloyed Perovskite Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26,27 ] Among them, CsPbI 3 is widely used due to its optimal bandgap ( E g ≈ 1.73 eV), high dielectric constant, large absorption attenuation coefficient, strong fluorescence, and long‐range electron transport. [ 28–31 ] CsPbI 3 perovskite quantum dots (PQDs) were used for perovskite solar cells, [ 32–36 ] light‐emitting diodes, [ 37–39 ] and even fullerene‐based OSCs. [ 40 ]…”
Section: Figurementioning
confidence: 99%